Mortuary behaviour and cultural practices in pre-colonial West Central Africa: new data from the Iroungou burial cave, Gabon. (August 2021) - Villotte, Sébastien; Kacki, Sacha; Mounier, Aurélien; Mora, Pascal; Espinasse, Loic; Dempano, Jules Zamke; Gerin, Christian; Meunier, Quentin; Oslisly, Richard
Abstract: Abstract : This study presents preliminary results of recent explorations at Iroungou (Gabon), a pre-colonial burial cave containing scattered skeletal remains of at least 28 men, women and children. The individuals, whose crania show cultural tooth ablation, were buried with abundant metallic objects, a combination with no known equivalent in West Central Africa.